Therapeutic effects of tyroservatide on metastasis of lung cancer and its mechanism affecting integrin–focal adhesion kinase signal transduction - Huang YT; Zhao L; Fu Z; Zhao M; Song XM; Jia J; Wang S; Li JP; Zhu ZF; Lin G; Lu R; Yao Z (Dove Medical Press, 2016)
Yu-ting Huang,1,* Lan Zhao,1,* Zheng Fu,1 Meng Zhao,1 Xiao-meng Song,1 Jing Jia,1 Song Wang,1 Jin-ping Li,1 Zhi-feng Zhu,1 Gang Lin,1,2 Rong Lu,1,2 Zhi Yao1,3 1Department of Immunology, Tianjin Medical University, Tianjin, 2Shenzhen Kangzhe Pharmaceutical Co., Ltd., Shenzhen, 3Key Laboratory of Immuno Microenvironment and Disease of the Educational Ministry of China, Tianjin Medical University, Tianjin, People’s Republic of China *These authors contributed equally to this paper Abstract: Tyroservatide (YSV) can inhibit the growth and metastasis of mouse lung cancer significantly. This study investigated the therapeutic effects of tripeptide YSV on metastasis of human lung cancer cells and explored its possible mechanism that affects integrin–focal adhesion kinase (FAK) signal transduction in tumor cells. YSV significantly inhibited the adhesion and the invasion of highly metastatic human lung cancer cell lines 95D, A549, and NCI-H1299. In addition, YSV significantly inhibited phosphorylation of FAK Tyr397 and FAK Tyr576/577 in the 95D, A549, and NCI-H1299 human lung cancer cells in vitro. And the mRNA level and protein expression of FAK in these human lung cancer cells decreased at the same time. YSV also significantly inhibited mRNA and protein levels of integrin ß1 and integrin ß3 in the 95D, A549, and NCI-H1299 human lung cancer cells. Our research showed that YSV inhibited adhesion and invasion of human lung cancer cells and exhibited therapeutic effects on metastasis of lung cancer. Keywords: tyroservatide, integrin, focal adhesion kinase, FAK, MMP-2, MMP-9